Evaluating the impact of indoor aerosols on the performance of real-time radon sensors - Rey, Joan F.; Meisser, Nicolas; Licina, Dusan; Goyette Pernot, Joëlle (Frontiers in Built Environment, 2024)
Radon, a naturally occurring radioactive gas, poses a significant health risk by accumulating in buildings and potentially leading to lung cancer. Depending on building construction and geographical location, radon levels can vary substantially both within individual buildings and between different buildings. While previous studies have primarily focused on the impact of temperature and relative humidity on radon devices, the influence of aerosols remains largely unexplored. This paper presents a comprehensive evaluation of the influence of indoor aerosol sources on the performance of real-time radon sensors, encompassing consumer, medium, and research-grade devices. Measurements were performed at relatively low (300 Bq/m 3 ) and high (2'000-3'000 Bq/m 3 ) radon levels in a controlled environment-a stable atomic shelter with constant temperature and humidity conditions. Six different aerosols sources were introduced to produce aerosols of different sizes and concentrations. The results suggest that the tested indoor aerosols did not significantly influence the performance of radon devices, irrespective of their grade or detection method. Consequently, sensor performance and the radon levels being investigated may exert a more significant influence on the obtained results than aerosol levels alone. This paper provides valuable insights into the influence of indoor environment on the performance of radon measuring devices, underscoring the importance of understanding their utility and application scope for researchers, professionals, and the general public alike.